Major References for Learning About Healthy Eating: Differences Between Canadian Anglophone and Francophone Men and Women. (May 2017) - Ahmadi, Davod; Sinclair, Kate; Ebadi, Narges; Helal, Gabrielle; Melgar-quinonez, Hugo
This study examined associations between main references Anglophone and Francophone men and women refer to when learning healthy eating, and their knowledge of best food habits (KBFH), body mass index (BMI) status, sex, age, education, and household income. Data were obtained from a 2012 Statistics Canada survey (Canadian Community Health Survey: Rapid Response, Canada's Food Guide). A greater number of women reported high KBFH than men. Regardless of the language group, "general search on the Internet, " "TV programs, " and "family and friends" were referred to the most for learning about healthy eating. However, those who refer more often to "health organizations" or "weight loss programs" had significantly higher KBFH and lower BMI rates.